Disaster Threats in the Gunungsewu Karst Area and Mitigation Efforts in the Framework of Disaster Risk Reduction Review of the Hydrological and Geomorphological Aspects - Wijayanti, Pipit; Noviani, Rita (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Karst is identical with arid, rocky areas and often drought disasters every year. Besides the drought, there are several hazards in the karst area.  This study aims to review the various hazards that occur in the Gunungsewu Karst area and mitigation efforts that can be done. Multiple hazards are base on karst hydrological and geomorphological characteristics. This study is base on a literature review in several related studies, both in karst areas and in the research in the same area. Based on the results of the study, it was found that there are four types of hazards found in Gunungsewu Karst areas, namely drought, flooding, pollution, and collapse.  In general, mitigation efforts that can be carried out are mapping hazards, monitoring, and increasing the capacity of people in karst areas. However, mitigation efforts are specifically made based on the type of hazards. It was done so that the existing hazards do not pose a disaster risk.